Pengelompokan Provinsi Di Indonesia Berdasarkan Indikator Kesehatan Balita Menggunakan Metode Agglomerative Clustering - Ana Fikria; I Komang Gede Sukarsa; I Putu Winada Gautama; Made Ayu Dwi Octavanny; Anggun Yuliarum Qur’ani; Desak Putu Eka Nilakusmawati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Child Health is a crucial indicator in assessing the overall health of a population. However, there are disparities between provinces in terms of healthcare access, immunization coverage, and child nutrition status. Therefore, this study aims to cluster 38 provinces in Indonesia based on infant health indicators using the Agglomerative Hierarchical Clustering method. The data used is sourced from the 2023 Indonesian Health Profile Report, with variables including neonatal visit coverage, complete basic immunization, infant weighing, and the prevalence of infants with severe underweight, stunting, and malnutrition. The five agglomerative methods applied in this study are Single Linkage, Complete Linkage, Average Linkage, Centroid, and Ward. The results indicate disparities in child health conditions across provinces, with clusters representing regions with good, moderate, and poor conditions. These findings can serve as a reference for the implementation of the Free Nutritious Meal Program (MBG) in 2025 to better target areas with high vulnerability, in order to reduce stunting rates and improve overall child nutritional status.